Alternative Splicing in Self-Renewal of Embryonic Stem Cells - Clara Y. Cheong; Thomas Lufkin (Stem Cells International)
Much of embryonic stem cell biology has focused on transcriptional expression and regulation of genes that could mediate its unique potential in self-renewal or pluripotency. In alignment with our present understanding on the genetic, protein, and epigenetic factors that may direct cell fate, we present a short overview of the often overlooked contribution of alternative splice variants to regulatory diversity. Progressing beyond the limitations of a fixed genomic sequence, alternative splicing offers an additional layer of complexity to produce protein variants that may differ in function and localization that can direct embryonic stem cells to specific differentiation pathways. In light of the number of variants that can be produced at key ES cell genes alone, it is challenging to consider how much more multifaceted transcriptional regulation truly is, and if this can be captured more fully in future works.